(untitled) (INCH : Journal of Infant and Child Healthcare, 2023)
Assesment of the implementation of health services for pregnant women can be done by looking at the coverage of K4. This study aims to determine the factors associated with K4 coverage at the Minas Health Center, Siak Regency. This type of research is descriptive with design cross sectional. Held in January – May 2021 at the Minas Health Center, Siak Regency. The population of all pregnant women in the third trimester with a sample of 44 people, the sampling technique was purposive sampling. The research instrument was a questionnaire. Data analysis using test chi square. The results of data analysis showed that there was a relationship between age (p: 0.000), education (p: 0.007), knowledge (p; 0.001), family support (p: 0.043) and affordability of facilities (p: 0.041) with K4 coverage at the Minas Health Center. It is hoped that this research can be useful for health workers in increasing cross-program and crosssectoral collaboration so that the program can run properly.